HELP-5 : Evaluation of the implementation of a digital tool to survey the quality of life of cancer patients and the analysis of the outcome dimensions of the implementation - Isabelle Sophie Meyer (2023)
Cancer and mental health are currently the biggest health problems worldwide according to Covid-19. In order to cope with them, good tools of all kinds are needed and, among other things, digitalization must be continued. This work was done in cooperation with a project at the Medical Center Hamburg Eppendorf (UKE), which developed a digital questionnaire to survey the Health-related quality of life (HrQoL) of cancer patients at the UKE. In addition to the implementation of this questionnaire, tools were developed for the evaluation of the implementation based on the implementation outcome dimensions developed by Proctor et al. (2011). To what extent the questionnaire components used for the individual outcome dimensions provide a discriminating result and whether there are other factors influencing the implementation process. The methodology used was a factor analysis and a qualitative analysis of collected data. The result of the factor analysis showed that the queried implementation outcome dimensions are not selective. The qualitative evaluation provided evidence that survey timing and possible higher-level structures should be considered when developing appropriate evaluation instruments. In summary, this work demonstrates the need to develop more valid evaluation instruments for implementation of digital patient reported outcomes (PROs) to improve patient care and practitioner working conditions and to better address current health problems.